The Opportunity Offered by the ESSnuSB Project to Exploit the Larger Leptonic CP Violation Signal at the Second Oscillation Maximum and the Requirements of This Project on the ESS Accelerator Complex - E. Wildner; E. Baussan; M. Blennow; M. Bogomilov; A. Burgman; E. Bouquerel; C. Carlile; J. Cederkäll; P. Christiansen; P. Cupial; H. Danared; M. Dracos; et al. (Advances in High Energy Physics)
The European Spallation Source (ESS), currently under construction in Lund, Sweden, is a research center that will provide, by 2023, the world’s most powerful neutron source. The average power of the proton linac will be 5 MW. Pulsing this linac at higher frequency will make it possible to raise the average total beam power to 10 MW to produce, in parallel with the spallation neutron production, a very intense neutrino Super Beam of about 0.4 GeV mean neutrino energy. This will allow searching for leptonic CP violation at the second oscillation maximum where the sensitivity is about 3 times higher than at the first. The ESS neutrino Super Beam, ESSnuSB operated with a 2.0 GeV linac proton beam, together with a large underground Water Cherenkov detector located at 540 km from Lund, will make it possible to discover leptonic CP violation at 5σ significance level in 56% (65% for an upgrade to 2.5 GeV beam energy) of the leptonic CP-violating phase range after 10 years of data taking, assuming a 5% systematic error in the neutrino flux and 10% in the neutrino cross section. The paper presents the outstanding physics reach possible for CP violation with ESSnuSB obtainable under these assumptions for the systematic errors. It also describes the upgrade of the ESS accelerator complex required for ESSnuSB.